The effect of vaginal nitroglycerin and misoprostol on cervical dilation in women with term and post-term pregnancy: A randomized clinical trial - Maryam Ahmadi; Mahboobeh Goodini; Sajjad Daneshyar; Elham Khanlarzadeh (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: Cervical ripening is essential for vaginal delivery, therefore, a safe and appropriate method should be considered for cervical ripening. Today, various medical methods are used for cervical ripening, such as estrogen gels, prostaglandins, and nitroglycerine. However, the preference of one to the other is unknown. This study was performed aimed to compare the effects of vaginal misoprostol and vaginal nitroglycerine gelatin capsule on cervical ripening in term and post-term pregnancy.Methods: This trial study was performed in 2019 on 90 pregnant women with term and post-term pregnancies who were candidates for vaginal delivery induced by an unfavorable cervix (bishop score equal or <4) and referred to Fatemieh Hospital in Hamadan. Patients were divided into two groups of vaginal nitroglycerine and vaginal misoprostol. The data of the two groups related to demographics, dilatation, labor progress, newborn Apgar and postpartum bleeding were recorded in the forms through observation. Data were analyzed by SPSS software (version 20) and T-test, Chi-square, and Fisher tests. P<0.05 was considered statistically significant.Results: The rate of cervical ripening in the nitroglycerine group was significantly higher than the misoprostol group (P<0.05). The incidence of side effects such as headache, hypotension, and postpartum bleeding before and after delivery was 6 cases (13%) in the nitroglycerin group and 12 cases (33.3%) in the misoprostol group, which was statistically significant (p<0.05). Moreover, the active phase of labor was significantly shorter in the misoprostol group than the nitroglycerin group (p<0.05).Conclusion: vaginal nitroglycerine gelatin capsule with a suitable dose can cause rapid and transient softening of the cervix and can help to vaginal delivery. The side effects of vaginal nitroglycerine gelatin capsule are more limited and controllable than the side effects of vaginal misoprostol.